2003
DOI: 10.1067/mva.2003.55
|View full text |Cite
|
Sign up to set email alerts
|

Intrasac flow velocities predict sealing of type II endoleaks after endovascular abdominal aortic aneurysm repair

Abstract: Intrasac Doppler velocities can be used to predict whether a type II endoleak will spontaneously seal. High-velocity type II endoleaks are related to preoperative large branch vessel diameter and number and are resistant to endovascular treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 14 publications
0
61
0
2
Order By: Relevance
“…Several studies reported that 10.5% of the patients that underwent EVAR died due to any reason [2,5,[7][8][9], probably due to the high age of the patients and co-morbidity that was pre-existent before EVAR. The current definition of procedure-related mortality according to the Reporting Standards has not been evaluated so far.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported that 10.5% of the patients that underwent EVAR died due to any reason [2,5,[7][8][9], probably due to the high age of the patients and co-morbidity that was pre-existent before EVAR. The current definition of procedure-related mortality according to the Reporting Standards has not been evaluated so far.…”
Section: Introductionmentioning
confidence: 99%
“…The risk of aneurysm rupture in patients with pure type II endoleak is not increased compared with patients with no endoleak [4,14]. In a comparison of three groups of patients with type II endoleaks-those with a persistent type II endoleak, those with a transient (\1 month) type II endoleak, and those with no endoleak-Arko et al found that aneurysms with a persistent type II endoleak increased in diameter and volume compared with the two other groups, both of which decreased [36]. There were no aneurysm ruptures in patients with type II endoleak and no correlation between type II endoleaks and stent graft migration, proximal neck enlargement, or aneurysm.…”
Section: Natural History Of Aneurysms With Endoleakmentioning
confidence: 99%
“…Type II endoleaks are often seen immediately after placement of an endovascular device, and are more likely to be seen and persist in patients with large IMA or multiple lumbar arteries [36]. The long-term significance of type II endoleaks is unknown.…”
Section: Natural History Of Aneurysms With Endoleakmentioning
confidence: 99%
“…Certain characteristics such as high intrasac velocity and the high pressure of type II endoleaks have been reported to associate with resistance in sac shrinkage, though neither can exclusively predict their impact on sac behavior. 2,9,10 Beeman recently reported that the existence of multiple type II endoleaks, as well as the accompanying bidirectional Doppler waveform, predicts more accurately the hemodynamic inhibition to aneurysm sac shrinkage, since this finding reflects the lack of an outflow vessel capable of reducing the flow resistance and, thus, the intrasac diastolic pressure. 11 Interestingly, contrast-enhanced ultrasound ( Figure 2) has been identified as a high-sensitive modality for the detection and hemodynamic characterization of type II endoleaks, differentiating sufficiently hypodynamic (prolonged washout time) lumbar endoleaks associating with post-EVAR sac increase.…”
Section: Evaluating the Role Of Endoleaksmentioning
confidence: 99%